FEMINIST INSTITUTIONALISM AS A MAJOR TREND IN GENDER INEQUALITY RESEARCH - Varych, Dmytro (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The development of gender equality is studied through the prism of feminist institutionalism, which combines institutional analysis with feminist criticism. The main attention is paid to the mechanisms of formation of gender norms and their impact on social processes. The role of social networks in shaping public discourse on gender issues is analyzed, as well as historical and contemporary approaches to gender equality, including the ideas of John Stuart Mill and their influence on the development of contemporary theories. The interaction of formal and informal institutional practices that affect the position of women in politics, economics and society is considered. The mechanisms through which gender stereotypes are entrenched in institutional structures are studied, as well as the prospects and strategies for overcoming them. Special attention is paid to the analysis of legal initiatives and international standards in the field of gender equality, as well as their impact on political and social reforms. The importance of a comprehensive approach to the analysis of gender inequality is emphasized, taking into account political, social and economic factors. Special attention is paid to approaches to institutional research in the social sciences, their common elements and fundamental differences. The significance of feminist institutionalism as a new approach to the analysis of institutions in the context of gender equality is argued. Special emphasis is placed on the need to transform social norms and values, which will contribute to the formation of an equal environment for all citizens. The study also considers examples of successful practices in combating gender inequality in different countries. Thus, a comprehensive overview of the main challenges and prospects for the development of gender equality in the modern world is provided.